No effect of beetroot juice supplementation on 100-m and 200-m swimming performance in moderately trained swimmers - Esen, O.; Nicholas, C.; Morris, M.; Bailey, S. J. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Dietary nitrate supplementation has been reported to improve performance in kayaking and rowing exercise, which mandate significant recruitment of the upper-body musculature. Because the effect of dietary nitrate supplementation on swimming performance is unclear, the purpose of this study was to assess the effect of dietary nitrate supplementation on 100-m and 200-m swimming freestyle time-trial (TT) performance. Methods: In a double-blind, randomized crossover design, 10 moderately trained swimmers underwent 2 separate 3-d supplementation periods, with a daily dose of either 140 mL nitrate-rich (~800 mg/d nitrate) or nitrate-depleted (PLA) beetroot juice (BRJ). After blood sampling on day 3, the swimmers performed both 200-m and 100-m freestyle swimming TTs, with 30 min recovery between trials. Results: Plasma nitrite concentration was greater after BRJ relative to PLA consumption (432 [203] nmol/L, 111 [56] nmol/L, respectively, P=.001). Systolic blood pressure was lowered after BRJ compared with PLA supplementation (114 [10], 120 [10] mm Hg, respectively P=.001), but time to complete the 200-m (BRJ 152.6 [14.1] s, PLA 152.5 [14.1] s) and 100-m (BRJ 69.5 [7.2] s, PLA 69.4 [7.4] s) freestyle swimming TTs was not different between BRJ and PLA (P>.05). Conclusions: Although 3 d of BRJ supplementation increased plasma nitrite concentration and lowered blood pressure, it did not improve 100-m and 200-m swimming TT performance. These results do not support an ergogenic effect of nitrate supplementation in moderately trained swimmers, at least for 100-m and 200-m freestyle swimming performance.